Features of Sports Performance Related Injuries of Elite Track and Field Athletes in Lithuania - Linas Rekus; Lina Simaškaitė; Egidijus Šakalys (Lithuanian Sports University, 2018)
Background. Sports injuries have a huge impact on performance of athletes in competitions. A lot of athletes do not obtain full recovery after injuries, which leads to trauma recurrence or higher severity injuries. Being aware of dominating anatomical regions and frequencies of occurrence of these traumas could help to prevent it and to protect athletes' health. Methods. In 2013 Lithuanian professional athletes were asked to fill in questionnaires developed by using standardized  methodology  validated  by  the  IOC  and  implemented  by  the  IAAF  during  international  track  and field competitions. Data were collected, processed and analysed. Results were obtained using statistical methods, significance level of p ≤ .05 was considered statistically significant. Results. We investigated 33 athletes- sprinters and throwers (javelin and discus throwers, shot putters). They had 57 cases of traumatic injuries in one year period (2012-2013). Results of the study showed that injuries of lower extremity statistically significantly dominated comparing with upper extremity and head/trunk in both fields of sport. Injuries by anatomical region were: lower extremity - 67%, upper extremity - 12%, head and trunk - 21%. Most of all were injured: hamstrings 23%, inguinal 10.5%, lumbar 13% area. Comparing traumas between throwers and sprinters groups lower extremity injuries statistically significantly dominated in sprinters group, while upper extremity had been injured only in the throwers' group. Analysing severity of the injuries we noticed that moderate and mild injuries were dominating. Mild and moderate severity injuries appeared leading to a higher risk of re-injury than high severity traumas. Recurrence of the same injury was noticed only in the group of sprinters - 57.9% of sprinters repeatedly suffered mostly from hamstring and inguinal traumas. Conclusions. According to the results of this study, sports medicine physicians could predict potential localization and recurrence of injuries and collaborating with coaches and athletes prepare opportune training programs to avoid harm. Keywords:  sports injuries, recurring injuries, trauma, track and field athletics, sports medicine